Penilaian Semula Nilai Indeks Hakisan Hujan (R) Dalam Model Usle Dengan Menggunakan Sistem Maklumat Geografi - Omar, Mohamad Nazuhan (2015)
Soil erosion is a serious problem and it needed to be addressed. There are various methods used to estimate soil erosion and among them is the universal soil loss equation (usle). An r factor refers to the soil erosion process influences by the rain. In the usle model, there are several calculating methods of r factor, such as the method proposed by roose (1975). This study was conducted to estimate the usle soil erosion using the values proposed by roose, to test the accuracy of the r factor variables of usle model specified by roose (1975) that is 0.5p and to reevaluate the compatibility of the r factor. This study was conducted in lembangan sungai pelarit hulu and lembangan sungai jarum by using the annual rainfall data from 2001 to 2007. The data was analyzed using a geographic information system (gis). Results from previous studies recorded the highest observation data with a record of 13,249.61 tons/year 2001 and the lowest observed data of 3,573.95 tons/year 2006. Roose calculation methods shows the highest difference of soil loss estimated by 377.77% and the differences closest to the observed data is 28.84%. Results of the arithmetic method 0.185p x 1.73 provides a better estimated of soil loss with the highest percentage differences of 101.77% and the percentage closest to the observed data is 0.91%. The new value of r factor of 0.185p is better than 0.5p because it gives a better estimation of soil loss and it is more suitable to be applied in the study basin and malaysia.